THE POWER OF PLAY: PLAY ACTIVITIES AS AN EFFECTIVE STRATEGY TO IMPROVE EARLY CHILDHOOD ENGLISH SKILLS - Reni Sawitri; Eka Danik Prahastiwi (Universitas Darunnajah, 2026)
This study explores the role of play-based activities in improving English language skills among early childhood learners in the digital era, where children are increasingly exposed to passive learning through screens. The objective of this research is to analyze how structured play activities can enhance vocabulary, speaking, and listening skills in early childhood education. This study employed a qualitative descriptive approach involving 12 preschool children in one class over a period of 1–2 months. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that play-based learning activities such as singing, role play, and interactive games significantly improve children's English abilities, particularly in listening and vocabulary, while speaking skills show gradual development. The learning environment also became more engaging, increasing children’s participation, motivation, and confidence. The significance of this study lies in demonstrating that play-based learning provides a meaningful, enjoyable, and developmentally appropriate approach for language acquisition. In conclusion, integrating play into English learning effectively supports both linguistic and social development in early childhood